Forest Ecology and Conservation - Chakravarty, Sumit; Shukla, Gopal (IntechOpen, 2017)
This book is dedicated to forest ecology and conservation on ecological and conservation aspects of forest. The book is divided into two sections: the first section "Forest Ecology" with four chapters deals with forest ecological aspects, while the second section "Forest Conservation" with two chapters looks into new techniques for conserving the forests. This book will bridge the gaps in the knowledge about some new emerging issues on forest ecology and conservation. It will be an interesting and helpful resource to all those in the field of forestry working for its sustainable use and conservation.